(untitled) (International Scientific Journal Alfraganus, 2025)
The development of the pharmaceutical industry involves ensuring rapid and stable growth. This includes saturating the domestic market with high-quality, safe, and affordable medicines produced locally, expanding sources of local raw materials, and increasing the production of drugs that re- place imports.